NRG-HN003: Phase I and Expansion Cohort Study of Adjuvant Pembrolizumab, Cisplatin and Radiation Therapy in Pathologically High-Risk Head and Neck Cancer - Bauman, Julie E. (Cancers (Basel), 2021)
SIMPLE SUMMARY: The anti-PD1 monoclonal antibody pembrolizumab improves survival in recurrent/metastatic head and neck squamous cell carcinoma. Patients with locoregional, pathologically high-risk disease recur frequently despite adjuvant cisplatin–radiation therapy. Targeting PD1 may reverse immunosuppression induced by cancer, chemotherapy, or radiation therapy. We conducted a phase I trial with an expansion cohort (n = 20) to determine the recommended phase II schedule for adding fixed-dose pembrolizumab to standard adjuvant cisplatin–radiation therapy. Eligible patients had resected, human papillomavirus-negative, stage III–IV oral cavity, pharynx, or larynx cancer with extracapsular nodal extension or positive margin. A total of four dose-limiting toxicities were observed in 34 patients (fever, wound infection, diverticulitis, nausea). Three of four were successfully rechallenged with pembrolizumab. The recommended phase II schedule was declared as pembrolizumab 200 mg every 3 weeks for eight doses, starting one week before adjuvant CRT. The regimen was safe and feasible in the cooperative group setting. Further development is warranted. ABSTRACT: The anti-PD1 monoclonal antibody pembrolizumab improves survival in recurrent/metastatic head and neck squamous cell carcinoma (HNSCC). Patients with locoregional, pathologically high-risk HNSCC recur frequently despite adjuvant cisplatin–radiation therapy (CRT). Targeting PD1 may reverse immunosuppression induced by HNSCC and CRT. We conducted a phase I trial with an expansion cohort (n = 20) to determine the recommended phase II schedule (RP2S) for adding fixed-dose pembrolizumab to standard adjuvant CRT. Eligible patients had resected HPV-negative, stage III–IV oral cavity, pharynx, or larynx HNSCC with extracapsular nodal extension or positive margin. RP2S was declared if three or fewer dose-limiting toxicities (DLT) occurred in a cohort of 12. DLT was defined as grade 3 or higher non-hematologic adverse event (AE) related to pembrolizumab, immune-related AE requiring over 2 weeks of systemic steroids, or unacceptable RT delay. A total of 34 patients enrolled at 23 NRG institutions. During the first cohort, only one DLT was observed (fever), thus RP2S was declared as pembrolizumab 200 mg every 3 weeks for eight doses, starting one week before CRT. During expansion, three additional DLTs were observed (wound infection, diverticulitis, nausea). Of the 34 patients, 28 (82%) received five or more doses of pembrolizumab. This regimen was safe and feasible in a cooperative group setting. Further development is warranted.